Tree Structures for Adaptive Control Space in 3D Meshing - Jurczyk, Tomasz; Głut, Barbara (Computer Science, 2017)
The article presents a comparison of several octree- and kd-tree-based structuresused for the construction of control space in the process of anisotropicmesh generation and adaptation. The adaptive control space utilized by theauthors supervises the construction of meshes by providing the required metricinformation regarding the desired shape and size of elements of the mesh ateach point of the modeled domain. Comparative tests of these auxiliary structureswere carried out based on different versions of the tree structures withrespect to computational and memory complexity as well as the quality of thegenerated mesh. Analysis of the results shows that kd-trees (not present inthe meshing literature in this role) offer good performance and may becomea reasonable alternative to octree structures.